Analisis Sistem Informasi Akuntansi Penerimaan Kas Pada Pelayanan Rawat Inap Di Rumah Sakit X - Mafiroh Fitri Mulani; Diska Arliena Hafni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This study aims to analyze the income receipts accounting information system for inpatient services at X Hospital. This research applied a qualitative approach. The data sources used were primary and secondary data. Data collection was conducted through observation, interviews, and documentation. The results showed the application of income receipts accounting information systems for inpatient services had not been appropriate and effective. This could be seen from the unclear job description and authority in each division, and there was no proportional differentiation of duties and responsibilities. The application income receipts accounting information system was done manually and it had not used serial numbers. In addition, the cash had not been deposited to the bank and petty cash has not been implemented. This might lead to fraud in cash management and abuse of authority in each department.